Inside Back Cover: Self‐Assembly of Measles Virus Nucleocapsid‐like Particles: Kinetics and RNA Sequence Dependence (Angew. Chem. Int. Ed. 32/2016). Issue 32 (8th June 2016) - Milles, Sigrid; Jensen, Malene Ringkjøbing; Communie, Guillaume; Maurin, Damien; Schoehn, Guy; Ruigrok, Rob W. H.; Blackledge, Martin
Abstract : Measles virus genomes are packaged into helical nucleocapsids, comprising thousands of nucleoproteins binding the entire genome. In their Communication onpage 9356 ff., R. W. H. Ruigrok, M. Blackledge, and co‐workers demonstrate the self‐organization of recombinant nucleoproteins into long nucleocapsid‐like helices, simply upon addition of RNA, providing a simple and versatile tool for investigating assembly. Remarkably, this assembly depends strongly on RNA sequence.